Screening for WSMV Tolerance in Wild Wheat Relatives - Sawyer, Caleb; Nouri, Shahideh; Prakash, Ved; Zarzynska-Nowak, Alexandra (My University, 2023)
Wheat Streak Mosaic Virus (WSMV) is a serious viral pathogen causing significant crop yield loss in wheat growing regions across the globe. In the United States, Its impacts are most heavily felt in the Great Plains, causing significant economic repercussions. While WSMV is primarily vectored by the wheat curl mite, this vector is difficult to control due to its size, resistance to pesticides, rapid reproduction, and feeding effects on host plants. Alongside efforts made to control the vector, our research attempts to circumvent this challenge in a search for genetic resistance and tolerance in wild wheat to combat the disease. In this study, a large panel of Aegilops tauschii accessions were grown in controlled environment growth chambers, then mechanically sap inoculated with WSMV and symptom severity was measured at different points post-inoculation. Viral titers were measured from systemic leaves in inoculated plants via real-time quantitative PCR. Based on the viral concentration and symptom severity, several tolerant and susceptible lines have been identified and selected for the genome wide association study (GWAS). Further analysis will be performed comparing the miRNA profiles of selected tolerant and susceptible lines to better understand their genetic regulation differences. These results could lead to the development of WSMV tolerant commercially used varieties. This research can help prevent high yield loss, securing reliable production of the United State’s top cereal food grain production.
Keywords: Wheat; Virus; Wild relatives; qPCR; Viral titer; USDA NIFA 2019-67032-29071